2021
DOI: 10.3389/fneur.2021.658451
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Hemiplegia of Childhood: Genotype–Phenotype Correlations in a Cohort of 39 Italian Patients

Abstract: Alternating hemiplegia of childhood is a rare neurological disease characterized by paroxysmal movement disorders and chronic neurological disturbances, with onset before 18 months of age. Mutations in the ATP1A3 gene have been identified in up to 80% of patients. Thirty-nine patients [20 females, 19 males, mean age 25.32 years (7.52–49.34)] have been recruited through the Italian Biobank and Clinical Registry for Alternating Hemiplegia of Childhood. Demographic data, genotype, paroxysmal movement disorders, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…With whole exome sequencing (WES), we were able to end the diagnostic odyssey for this family. Some studies have shown that symptoms of AHC can be improved with the use of Flunarizine (Cordani et al, 2021 ; Kusunoki et al, 2020 ). Flunarizine is a selective calcium channel entry blocker with calmodulin binding properties and histamine H1 blocking activity (Upadhyay & Ali, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…With whole exome sequencing (WES), we were able to end the diagnostic odyssey for this family. Some studies have shown that symptoms of AHC can be improved with the use of Flunarizine (Cordani et al, 2021 ; Kusunoki et al, 2020 ). Flunarizine is a selective calcium channel entry blocker with calmodulin binding properties and histamine H1 blocking activity (Upadhyay & Ali, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Any of these dysfunctions may have an important long-term effect on children with AHC. The episodes of hemiplegic episodes tend to decrease as the child gets older, [1,2] and in a recent study by Cordani et al, [51] epileptic seizures were found in 24/39 (62%) of AHC patients, which may have a deleterious role in the course of the disorder. particularly if seizures are drug-resistant.…”
Section: Alternating Hemiplegia Of Childhoodmentioning
confidence: 99%
“…Despite the growing number of pathogenic variants described, the most extensive cohort studies conducted in various populations have shown that 3 variants account for approximately 60% of all cases. [51] The p.Asp801Asn variant is detected in 30%–43%, p.Glu815Lys is responsible for 16%–35%, and p.Gly947Arg is responsible for 8%–15% of cases. [6,52,53] Other gene mutations (CACNA1A, SLC1A3, and SLC2A1) have occasionally been related to AHC showing similar clinical presentations.…”
Section: Alternating Hemiplegia Of Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected children also develop dysautonomic symptoms that may require emergency cardiopulmonary resuscitation. Although flunarizine is effective in decreasing the frequency and magnitude of hemiplegic attacks ( Cordani et al, 2021 ), the medication does not necessarily prevent sudden unexpected death in epilepsy or cardiac arrhythmia ( Jaffer et al, 2015 ). Thus, the long-term outcomes of AHC need to be improved.…”
Section: Introductionmentioning
confidence: 99%